A comparative study on PPR-2008, Bangladesh and Asian Development Bank (ADB) procurement guidelines 2015: strength and weakness - Hasan, Mohammad Rabioul (BRAC University, 2019)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.